Isotopic half‐life and enrichment factor in two species of European freshwater fish larvae: an experimental approach. (14th March 2017) - Latli, Adrien; Sturaro, Nicolas; Desjardin, Nelson; Michel, Loïc N.; Otjacques, William; Lepoint, Gilles; Kestemont, Patrick
Abstract : Rationale: Stable isotope ratios of carbon and nitrogen are valuable tools for field ecologists to use to analyse animal diets. However, the application of these tools requires knowledge of the tissue enrichment factor (TEF) and half‐life (HL). We experimentally compared TEF and HL in two freshwater fish larvae. We hypothesised that chub had a better growth/tissue replacement ratio than roach, due to the use of a food closer to their natural diet. Methods: We determined the isotopic HL, the TEF and the contribution of growth or metabolic tissue replacement to dynamic isotopic incorporation. After yolk sac resorption, larvae were fed for 5 weeks with prey similar to their natural diet ( Artemia nauplii ) up to the isotopic equilibrium followed by Chironomid larvae. Stable isotope measurements were carried out using a continuous flow isotope ratio mass spectrometer coupled to an elemental analyser. Results: Changes in isotopic composition strongly followed the predictions of exponential growth and time‐dependent models. The isotopic HL varied between 8.2 and 12.6 days and the TEF of nitrogen and carbon ranged from 1.7 to 3.1 ‰ and from –0.9 to 1.2 ‰, respectively. The incorporation of dietary 13 C was due more to the production of new tissue (between 56 and 79%) than to the metabolic process. Chub allocated more energy to growth than roach and the Chironomidae diet contributed more to the consumers' growth than the Artemia diet. Conclusions: Metabolic rates seemed lower for chub than for roach, especially when they were fed with Chironomidae. A Chironomidae‐based diet would be more profitable to chub, and the high associated growth rate could increase the development of the fish larvae. The HL and TEF were in the range of those reported in the literature. These results will be helpful for field‐based studies, because they can help to increase the accuracy of models. Copyright © 2017 John Wiley & Sons, Ltd.